Activated pancreatic stellate cells can impair pancreatic islet function in mice. (August 2015) - Zang, Guangxiang; Sandberg, Monica; Carlsson, Per-Ola; Welsh, Nils; Jansson, Leif; Barbu, Andreea
Abstract Background. Pancreatic or islet fibrosis is often associated with activated pancreatic stellate cells (PSCs). PSCs are considered not only to promote fibrosis, but also to be associated with glucose intolerance in some diseases. We therefore evaluated morphological and functional relationships between islets and PSCs in the normal mouse pancreas and transplanted islets. Methods. Immunohistochemistry was used to map the presence of PSCs in the normal mouse pancreas and islets implanted under the renal capsule. We isolated and cultured mouse PSCs and characterized them morphologically by immunofluorescence staining. Furthermore, we measured their cytokine production and determined their effects on insulin release from simultaneously cultured islets. Results. PSCs were scattered throughout the pancreas, with occasional cells within the islets, particularly in the islet capsule. In islet transplants they were found mainly in the graft periphery. Cultured PSCs became functionally activated and produced several cytokines. Throughout the culture period they linearly increased their production of interleukin-6 and mammalian keratinocyte-derived chemokine. PSC cytokine production was not affected by acute hyperglycemia. Syngeneic islets co-cultured with PSCs for 24–48 h increased their insulin release and lowered their insulin content. However, short-term insulin release in batch-type incubations was unaffected after 48 h of co-culture. Increased islet cell caspase-3 activation and a decreased islet cell replication were consistently observed after co-culture for 2 or 7 days. Conclusion. Activated PSCs may contribute to impaired islet endocrine function seen in exocrine pancreatitis and in islet fibrosis associated with some cases of type 2 diabetes.